Determination of In Vivo efficacy and safety of zeolite as a new pleurodesis agent - Engin Sumer; Muhammed Hamitoglu; Alev Cumbul; Sina Ercan; Nurcan Bac; Ahmet Aydin (Toxicology Reports, 2022)
Pleural effusion, the pathological condition in which an abnormal amount of pleural fluid is accumulated in the small space between the visceral and parietal pleurae of the lungs, can be treated by pleurodesis, whereby the pleural space is obliterated. This effect can be achieved by chemical pleurodesis utilizing various reagents such as talc, an agent commonly employed in pleurodesis. Zeolites, microporous tectosilicates found in nature as minerals, can be used in a wide range of medical applications. Different zeolite compounds may exhibit variable efficacy and safety profiles, mainly depending on their particle size. In this study, we evaluated the efficacy and safety of zeolite pleurodesis. New Zealand rabbits were administered 400 mg/kg of either agent dissolved in 2 mL of isotonic saline solution by injection into their pleural cavity, and computed tomography images were obtained on postoperative day 26. Euthanization was conducted at the end of 28 days for histopathological evaluation. Furthermore, subacute toxicity and mutagenicity profiles of zeolite were analyzed. Our findings revealed that zeolite was able to induce an adequate inflammatory response to achieve successful pleurodesis. The adhesion profiles were in favor of zeolite when compared to talc pleurodesis. Moreover, none of the tested doses of zeolite induced subacute toxicity or mutagenesis. Collectively, our results suggested zeolite as an effective and safe pleurodesis agent.